2021
DOI: 10.1038/s41598-021-88152-4
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial impact of Covid-19 outbreak on Italian asthmatic children and their mothers in a post lockdown scenario

Abstract: Italy was the first European country to fight the Covid-19 outbreak. To limit the transmission of the virus, the Italian Government imposed strict domestic quarantine policies and temporary closure of non-essential businesses and schools from March 10th,2020. Although more and more literature is exploring the impact of the pandemic on non-referred children and families, only a few studies are focused on the psychosocial impact of Covid-19 in chronically ill children and their caregivers. The present study inve… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 32 publications
5
26
0
Order By: Relevance
“…As to the children, patients with cancer did not significantly differ from healthy peers in COVID-19-related worries, general psychological functioning, and anxiety symptoms, in line with the literature that reports unchanged psychological functioning for children with chronic diseases such as diabetes and asthma in the first lockdown [13,14]. A study on Dutch children with cancer observed no differences in health-related quality of life and fatigue between the pre-and early-COVID-19 periods; authors referred to children's experience in dealing with medical traumatic events and adequate care and support received to explain these results [38].…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…As to the children, patients with cancer did not significantly differ from healthy peers in COVID-19-related worries, general psychological functioning, and anxiety symptoms, in line with the literature that reports unchanged psychological functioning for children with chronic diseases such as diabetes and asthma in the first lockdown [13,14]. A study on Dutch children with cancer observed no differences in health-related quality of life and fatigue between the pre-and early-COVID-19 periods; authors referred to children's experience in dealing with medical traumatic events and adequate care and support received to explain these results [38].…”
Section: Discussionsupporting
confidence: 85%
“…No differences in psychological functioning emerged when comparing Italian asthmatic children to their healthy peers during the first lockdown, except for higher worry about COVID-19 contagion. Their mothers reported, instead, greater worry about contagion, resumption of activities, and a worsening in psychological wellbeing [14]. Other studies showed worsened children's psychological wellbeing: pediatric patients with chronic lung diseases and their parents had more pandemic-related concerns and anxiety symptoms [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 136 Psychological fatigue during a pandemic scenario is more prevalent in mothers of asthmatic children. 137 The increase and persistence of obsessive‐compulsive symptoms have shown the importance of close monitoring of the public's mental health. 138 The incidence and severity of physical intimate partner violence have also been increased during the COVID‐19 pandemic, and the victims were not referred to health care services until the late stages.…”
Section: Methodsmentioning
confidence: 99%
“…However, the American Academy of Allergy, Asthma, and Immunology stated that asthma may be a risk factor for hospitalization due to COVID‐19, especially in individuals aged 18–49 6 . Following this information in the literature, a study conducted in Italy showed that mothers of asthmatic children were more prone to anxiety and fear due to COVID‐19 than the healthy population 7 . Parents of children with asthma have increased anxiety levels, and changes have been observed in their attitudes and thoughts towards asthma compared to the pre‐pandemic period 8 …”
Section: Introductionmentioning
confidence: 96%